Digitalized Probabilistic Approach on Construction Bid Pricing: Case example of Vietnam - Nguyen, Tuan Anh (International Journal of Sustainable Construction Engineering and Technology, 2024)
A bidding process is one of the essential phases in any project life cycle, aiming at selecting the proper bidder/tender for the contracted job.  The potential bidder expects to win the bid contract by offering the project owner an appropriate bid proposal and significant added value. The literature stops short at comparing winning probability of construction bid among cost-related factors via exploiting digitalised statistic construction bid database. This paper aims to develop a probabilistic bid pricing approach to determine the probability of winning a bid contract associated with the expected value and standard deviation of the bid price. The paper then analyses the relationship between the winning probability and digitalised cost-related data from a construction bidder's point of view.  Those cost-related data include mark-up rate, ratio of low bid to pre-estimate, and bid-to-pre-estimate comparison rate.  Furthermore, in the context of Industry 4.0, the paper applies system thinking in exploiting digitalised construction bid databases from online platforms, showing potential for digital transformation on bid analysis of construction bidders in developing countries, including Vietnam.  The finding of this paper, based on the case example of the Vietnamese bidding database, presents that the lower the mark-up rate, rate of low bid to pre-estimate, and bid-to-pre-estimate rate, the higher chance of winning a bid.  The paper might be of interest to anyone who involves in the construction bidding process.